PEMBERDAYAAN ALUMNI FK UNISBA WILAYAH PRIANGAN TIMUR SEBAGAI UPAYA KONTRIBUSI PEDULI PESANTREN SEHAT DI LINGKUNGANNYA - Indriyanti, Raden Anita; Perdana, Rizki; Widiyanti, Alvira (Jurnal Abdi Insani, 2025)
Based on a preliminary survey, situational analysis and dialogue conducted by the FK Unisba service team and alumni at the Sabilunnajat Islamic boarding school, produced data that the need for information regarding health, especially clean and healthy living behavior, is still minimal. Seeing the high potential for medical graduates from Islamic educational institutions , it is appropriate to make various efforts by FK Unisba alumni to solve health problems in Islamic boarding schools. The aim of this activity is to make efforts to empower FK Unisba Alumni in improving the health of students at the Sabilunnajat Islamic boarding school through training healthy student cadres. The method of this activity consists of a preparatory stage in form of a Focused Group Discussion by FK UNISBA alumni to identify problems in the Islamic boarding school environment, followed by an implementation stage through health screening and therapy, provision of health facilities, counseling for santri and training for healthy santri cadres. The activity ended with the reporting stage to assess the success of the training of healthy santri cadres. The results of this PKM activity are a reduction in health problems, the availability of health facilities, and the formation of  health cadres  as an effort to overcome early stage health problems in the Sabilunnajat Islamic boarding school environment. The importance of the role of partnership and cooperation between various parties, especially the Islamic boarding school comittee, the UNISBA Medical Faculty, the contribution of alumni and authorities in policy making, is the key to the success in improving the level of health in the surrounding environment.